Diagnosis and management of type 2 diabetes in children. Issue 7 (July 2022) - Garvick, Sarah; Altenburg, Lilli; Dunlap, Bailey; Fisher, Abby; Watson, Amanda; Gregory, Tanya
ABSTRACT: The incidence of type 2 diabetes in children has risen 4.8% over the past decade, correlating with steadily rising obesity rates in children. Updated guidelines from the American Academy of Pediatrics and the American Diabetes Association encourage early identification and pharmacologic intervention for children with type 2 diabetes. Because of the aggressive disease course in children, comprehensive treatment must include prevention of complications such as diabetic nephropathy and neuropathy as well as management of comorbidities such as cardiovascular disease and dyslipidemia. Because the highest incidence of type 2 diabetes is reported in patients from racial or ethnic minority groups and those of low socioeconomic status, clinicians must work with patients and families to identify socioeconomic disparities that could affect adherence to diabetes management plans and to connect patients with community resources.